Book review: Environmental DNA: For Biodiversity Research and Monitoring by Pierre Taberlet, Aurélie Bonin, Lucie Zinger and Eric Coissac. Issue 20 (3rd October 2019) - Chariton, Anthony A.
Abstract : As readers of Molecular Ecology are aware, over the past decade environmental DNA (eDNA) techniques has changed the field of ecology. This is especially the case in biological composition studies where the size or degradation of the sample limits the usefulness of morphological based approaches, e.g., microbial communities and gut‐diet analysis. While there are numerous excellent books on molecular ecology, most lack sufficient detail to both inform and guide researchers through each step of an eDNA study, from conception to analysis. The authors of Environmental DNA (Taberlet, Bonin, Zinger, & Coissac, 2018) aim to address this gap by focusing specifically on eDNA research and its applications, providing a vehicle which not only clearly articulates the basics to those unfamiliar with the field, but also provides an incredible amount of detail with regards to designing and performing metabarcoding studies. As articulated by the authors, Environmental DNA is essentially a practical handbook which aims to provide the reader with the appropriate level of background information, theory and guidance to perform high quality eDNA research. The book is squarely aimed at graduate, post‐graduate students and researchers from the biological sciences, and requires no prior knowledge in molecular ecology per se. However, I have also found the book equally useful for nonmolecular scientists, enabling them to understand the requirements for implementing robust eDNA metabarcoding monitoring programs.